Social change and violence : the Indian experience - Rajgopal, P. R.; Centre for Policy Research (New Delhi, India) (New Delhi : Uppal Pub. House, 1987)
Study with reference to several states, chiefly in the context of caste and land tenure.
"Under the auspices of Centre for Policy Research."
Keywords: Violence -- India; India -- Social conditions -- 1947-